A novel missense mutation c.1381T>C: p.(S461P) in POLE causes multiple molecular features of endometrial carcinoma in China: a case report - Li, Yingxue; Wang, Li; Han, Lin; Zheng, Zheng; Yan, Jinqiang (Frontiers in Oncology, 2025)
BackgroundAccurately determining the pathogenicity of newly discovered POLE mutations is crucial for the precise molecular classification of endometrial carcinoma.MethodsIn one patient with endometrial carcinoma, next-generation sequencing (NGS) was performed to detect variants in POLE, TP53, BRCA1/2, CTNNB1, EPCAM, MLH1, MSH2, MSH6, and PMS2, as well as microsatellite instability (MSI) status in the tumor tissues. Variant interpretation followed ACMG/AMP guidelines, integrating evidence from literature, established guidelines, public databases, and clinical studies. Immunohistochemistry was used to evaluate MLH1, PMS2, MSH2, MSH6, and p53 protein expression in tumor tissues.ResultsWe successfully identified a novel potential missense mutation, c.1381T>C: p.(S461P), in exon 14 of POLE. This variant, reported here for the first time in endometrial carcinoma, was preliminarily classified as likely pathogenic based on available evidence. Additional variants were detected: TP53: c.844C>T: p.(R282W), TP53: c.711G>A: p.(M237I), and MSH6: c.3103C>T: p.(R1035*). The MSI status was classified as MSI-L. Immunohistochemistry revealed MLH1 (+), PMS2 (+), MSH2 (+), MSH6 (−), and p53 expression consistent with a mixed pattern (80% tumor region wild type, 20% region mutant subtype).ConclusionThis is the first report of the POLE (c.1381T>C: p.(S461P)) variant in endometrial carcinoma. We analyzed its potential pathogenic mechanism, which may contribute to the complex molecular phenotype of POLEmut + MMRd + p53abn tumors, and expanded the POLE mutation spectrum by adding a new likely pathogenic site.